220GHz detection using 035 uM AMS mosfet as sub-THz detector Drain bias detraction - Mohd Azlishah, Othman; I., Harrison (2012)
In this paper we present the detection of sub-THz radiation at 220 GHz by using 0.35 μm AMS Metal Oxide Semiconductor Field Effect Transistor (MOSFET). The design procedure and experimental setup are shown in order to design and characterize the MOSFETs photoresponse. The experiment and observation of photoresponse are measured against gate voltage with a drain current bias detraction at room temperature. The measured photoresponse is a superposition of a generally increasing response with a decrease in V cs coupled with a small peak approximately at threshold and there is evidence that the MOSFET can be a sensitive sub-THz detector in the room temperature.